United States : 2005 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2005)
The 2005 Article IV Consultation for the United States reports that robust productivity growth and high corporate profits have contributed to a strong rebound in business investment and some acceleration in employment. The financial sector appears well positioned to provide continued support to the recovery. Equity prices have risen, long-term interest rates remain low, banks are well capitalized and highly profitable, and indicators of credit quality remain strong. The robust housing market has caused financial regulators to tighten oversight of home equity and other residential loans.